Optimisation of Indoor Spatial and Temporal Aspects of Deep Architectural Studio on Visual Comfort - Rizky Amalia Achsani; Surjamanto Wonorahardjo; Sugeng Triyadi (Journal of Daylighting)
Visual comfort in deep rooms with side lit openings varies by positions and time; thus, interventions are required to provide comfort for all users in a room. This study aims to identify the conditions affecting visual comfort and potential interventions on spatial and temporal aspects of a room. This experiment comprises two layout settings: semi-enclosed studio layout and open studio layout with variables of zone (perimeter and core), viewing direction (north window, east wall, south window, and west wall), and temporal aspect (morning, midday, and afternoon), which determines how each aspect influences visual comfort. In this study, visual comfort is indicated using vertical eye illuminance (Ev) and daylight glare probability (DGP). Field measurements of daylighting performance were taken over five days and three times per day using a light meter to capture Ev and HDR images, which were then processed using Aftab Alpha software to produce DGP values. The results indicate that visual comfort in a deep room sequentially depends on view direction, zone, layout, and time. The value of Ev in deep rooms is significantly influenced by the type of opening, specifically the side lighting, which results in short penetration and does not reach the room core. Additionally, it depends on outdoor conditions. Consequently, the value at the perimeter is much higher than that at the core. By contrast, the glare sensation was not influenced by outdoor conditions during the day. Adjusting the view direction can control the less-than-ideal sitting position to obtain visual comfort. Additionally, correcting the sitting position in the zone can improve visual comfort at various times. Obstruction in the room plays a positive role in controlling glare and plays a negative role when reducing Ev. The period of visual discomfort throughout the day identified that the worst conditions occur in the morning owing to the lack of Ev. The optimum condition occurs during the day in the west wall and south window view direction, south perimeter zone, and semi-enclosed studio layout. Therefore, view direction and zone are effective features for obtaining visual comfort. Nevertheless, the layout type, room surface properties, and obstruction can also enhance visual comfort in various time conditions such as in the morning, afternoon, or evening. Horizontal plane components such as ceilings can expand the effects of Ev and reduce the effects of DGP in the morning or on cloudy days. The findings have implications for the design of deep rooms such as offices, studios, museums, and galleries in arranging the characteristics of horizontal and vertical surfaces of furniture and layout room that can affect the performance of the user.